Sports brand storymaking: An investigation of the process of co-created brand storytelling in the sporting goods industry, by the case of adidas - Hackenberger, Charlotte (2017)
The dissertation explores the evolving concept of sports brand storymaking as a highly relevant future branding and communications tool for the sporting goods industry. In response to increasing consumer involvement, the term of brand storymaking refers to brand storytelling in the context of co-creation. Despite the high relevance and prominence of its underlying principles - brand storytelling and co-creation - the academic literature review has revealed a research gap on the emerging concept of brand storymaking. This makes the need for exploratory research apparent with the aim to assess the research question: "How can a process model of the sports brand storymaking process in social media be defined in an ideal way (by analyzing the case of adidas)"? Against the background of academic literature and based on a selected reference framework, empirical research has been done in cooperation with the German sporting goods company adidas. For the purpose of the research, an exploratory inductive approach was chosen to illuminate the process of sports brand storymaking as a new phenomenon. As the selected qualitative method, an embedded single-case study with two units of analysis - "adidas Football and adidas Originals" - was conducted. By performing a two-tier content analysis of (1) social media data and (2) in-depth expert interviews, the reference framework could be validated as an appropriate preliminary process model for brand storymaking in social media and the final extended process model evolved. Ultimately, the final model for the sports brand storymaking process in social media has been reviewed in the light of academic and managerial contributions, current limitations and future research directions.